Comparação analítica e experimental: parâmetros de projeto e curvas tensão versus deformação para concreto com fibras de aço - Dantas, Lucas Ramos (Universidade Federal Rural do Semi-Árido, 2017)
Even though it is a widely used material, the weakness of the concrete can considerably affect the durability of the structural element. The addition of fibers is one of the alternatives to alter the fragile characteristics of the concrete and extend its useful life. The aim of this work is to compare the proposed by institutions and national and international normative references, in relation the design bases and stress-strain curves, with the experimental uniaxial compression data, verifying the main divergences and the efficiency of the steel fibers in the cement matrix. It will be approached concepts about the behavior to compression of the common concrete and addition of fibers, the operation of the fiber-matrix mechanism, effects of the load duration on axial tests and the analytical mathematical models proposed in the literature.
Keywords: Curvas Tensão-Deformação; Stress-strain Curves; Comportamento à Compressão; Behavior to Compression; Concreto com Fibras de Aço; Concrete with Steel Fibers; Ensaios Uniaxiais de Compressão; Uniaxial Compression Tests; ENGENHARIAS::ENGENHARIA CIVIL